SOSIALISASI PENGUATAN KEWIRAUSAHAAN ATAS DASAR SPIRITUAL DALAM OPTIMALISASI KAMPUNG TANGGUNG ALBA MALANG - Choirul Anam; Adya Hermawati; Survival (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2021)
Small businesses have a function and role in the development of theeconomic field. One way to create employment opportunities can be doneby developing a business (industry), namely through the development ofsmall businesses (industries). The result of socialization of communityservice activities is the optimization of pioneered businesses, committedto entrepreneurship, creating economic value in every business, andcreating jobs. And, spiritual values Always close to Allah, Always PresentAllah in life, business; Allah regulates everything in life, business; Trust inAllah; Leave all business to Allah; Trust in Allah; Love Allah with all myheart; Allah knows all human needs